Plasma Fibroblast Growth Factor 23: Clinical Correlates and Association With Cardiovascular Disease and Mortality in the Framingham Heart Study. Issue 7 (July 2016) - Haring, Robin; Enserro, Danielle; Xanthakis, Vanessa; Mitchell, Gary F.; Benjamin, Emelia J.; Hamburg, Naomi M.; Sullivan, Lisa; Nauck, Matthias; Wallaschofski, Henri; Vasan, Ramachandran S.
Abstract : Background: Fibroblast growth factor 23 (FGF23) is emerging as a novel biomarker of bone metabolism, chronic kidney disease, and cardiovascular disease (CVD). However, its clinical correlates and potential predictive role in a community‐based setting are incompletely understood. Methods and Results: We evaluated participants of the Framingham Heart Study (seventh examination cycle of the Offspring cohort plus second examination cycle of the multiethnic Omni cohort) to identify clinical correlates of plasma FGF23 (N=3236) and examine its cross‐sectional association with vascular function (N=2209), and longitudinal association with 10‐year incidence of CVD (N=2823), and all‐cause mortality (N=3223). Circulating FGF23 concentrations were positively related to African‐American and Asian ethnicity, waist circumference, current smoking, serum glucose, history of CVD, and antihypertensive medication use; and negatively related to male sex, hormone replacement therapy, and estimated glomerular filtration rate. Multivariable‐adjusted cross‐sectional analyses showed no consistent association of FGF23 with vascular function measures. During a median follow‐up time of 10.8 years, 347 incident CVD events and 412 deaths occurred. Multivariable‐adjusted Cox regression models revealed a positive association of FGF23 with all‐cause mortality (hazard ratio [HR] per SD increase, 1.31; 95% CI, 1.20–1.42), but not with incident CVD (HR per SD increase, 1.05; 95% CI, 0.94–1.17). Conclusions: In our large, community‐based sample, FGF23 was associated with mortality risk, but not with vascular function or incident CVD.